1994
DOI: 10.1677/joe.0.1400313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone on steroidogenesis, insulin-like growth factor-I (IGF-I) and IGF-binding protein-1 production and DNA synthesis in cultured human luteinized granulosa cells

Abstract: Numerous clinical and experimental observations have suggested that GH is important in ovarian function. We have investigated the effect of GH alone and GH in combination with FSH on the secretion of oestradiol, progesterone, insulin-like growth factor-I (IGF-I) and IGF-binding protein-1 (IGFBP-1) and on [3H]thymidine incorporation in cultured human luteinized granulosa cells. Granulosa cells from patients undergoing treatment for in vitro fertilization were isolated and cultured for 2 days in culture medium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 12 publications
4
27
0
3
Order By: Relevance
“…GH administration in vivo similarly increases the number of large follicles in pigs (DeLaSota et al 1993 and GH-deficient dwarf rats (Ozawa et al 1996) and the number of corpora lutea in cattle (Lucy et al 1992) and GH transgenic rats (Danilovich et al 2000). The stimulatory effect of GH on follicle number and size reflects increased cell proliferation, at least in luteinized human granulosa cells (Ovesen et al 1994), but also is indicative of the suppressive effect of GH on apoptosis (Eisenhauer et al 1995, Sirotkin & Makarevich 1999, Danilovich et al 2000. GH may enhance follicular survival and cell proliferation by potentiating LH action, since GH deficiency is associated with decreased LH receptor gene expression and LH…”
Section: Folliculogenesis and Gametogenesismentioning
confidence: 99%
“…GH administration in vivo similarly increases the number of large follicles in pigs (DeLaSota et al 1993 and GH-deficient dwarf rats (Ozawa et al 1996) and the number of corpora lutea in cattle (Lucy et al 1992) and GH transgenic rats (Danilovich et al 2000). The stimulatory effect of GH on follicle number and size reflects increased cell proliferation, at least in luteinized human granulosa cells (Ovesen et al 1994), but also is indicative of the suppressive effect of GH on apoptosis (Eisenhauer et al 1995, Sirotkin & Makarevich 1999, Danilovich et al 2000. GH may enhance follicular survival and cell proliferation by potentiating LH action, since GH deficiency is associated with decreased LH receptor gene expression and LH…”
Section: Folliculogenesis and Gametogenesismentioning
confidence: 99%
“…The data suggest that BST treatment directly stimulates ovarian function. Indeed, in vitro studies have described direct actions of GH on follicular and luteal cell functions; GH, either alone or accompanied by follicle stimulating hormone (FSH) or estradiol-17β (E 2 ) [7][8][9][10][11], stimulates granulosa cell steroidogenesis, and with insulin, stimulates the proliferation of granulosa cells [9]; GH also stimulates P production by human luteal cells [12], and the release of P from the microdialyzed bovine CL in vitro [13]. On the other hand, studies on the GH receptor in the bovine ovary have indicated that the CL is the major site for GH receptor protein and its mRNA in the ovary, whereas the follicles have almost no GH receptors [14,15].…”
mentioning
confidence: 99%
“…O GH estimula a síntese de progesterona e estrogênio. A ação do GH na esteroidogê-nese está associada ao aumento da atividade de muitas enzimas e pode ser parcialmente responsável pelo efeito facilitatório do GH sobre a foliculogênese e gametogênese (14); o GH estimula a esteroidogênese na espécie humana por ação direta independente da IGF-1 (16). As pacientes neste estudo apresentavam níveis de estradiol inferiores a 13pg/ml, afastando uma secreção estrogênica importante e contínua.…”
Section: Relato Dos Casos Relato Dos Casosunclassified